Analysis of stakeholder in the development of Labombo Beach sustainable town in Palopo City - Muhammad Bibin; Yon Vitner; Zulhamsyah Imran (Faculty of Social and Political Science, Universitas Airlangga, 2018)
Labombo Beach is one of the main Palopo City natural tourism. This study aimed to understand the participation of stakeholder in the development of marine tourism in Labombo Beach. The stakeholders that included in this research are the governmental institutions, non-governmental organization, and socialcommunities. Those stakeholders are being observed in drawing up policies for proper management and development in Labombo Beach tourist area. The method of this study is used two analytical approaches, qualitative stakeholder analysis and Analytical Hierarchy Process (AHP). The results showed that Tourism Department of Palopo City as a mandated agency in government affairs of tourism management and development in Palopo City as well as one of the key players which can fully engage other key players in formulating and evaluating the strategy of maritime tourism development of Labombo Beach. Tourism Department of Palopo City also maintaining a great communication and monitoring the existence of stakeholder actors group (A conscious group of youth lovers of nature and the environment of Palopo City and the community) because that their interests and influence can change in over time. The alternative development of Labombo Beach marine tourism which become the first priority is making tourism zoning, second is improving tourism facilities and infrastructure, third is conducting a tourism promotion and fourth is increasing the foster and train within the community.